Penguatan Personal Branding Mahasiswa Universitas Negeri Makassar Melalui Optimalisasi Media Sosial - Ilma Wulansari Hasdiansa; Hasbiah, Sitti; Aswar, Nurul Fadilah; Riu, Isma Azis; Rauf, Deddy Ibrahim (Pemberdayaan Masyarakat : Jurnal Aksi Sosial, 2025)
Social media has become the primary platform for students to express themselves and build their professional reputation. However, many students have not yet fully utilized social media to support their careers and academic image. This community service activity aims to enhance the understanding and skills of students at the University of Makassar (UNM) in building a strong personal brand through social media. The implementation method includes socialization, training, and direct mentoring for students at the Faculty of Economics and Business, UNM. The evaluation was conducted using pre-tests and post-tests to measure the improvement in knowledge and skills of the participants. The results show a significant increase in students' understanding, with the average score improving from a moderate level to an excellent level. Moreover, the majority of participants have begun to apply personal branding content strategies on their social media platforms. This training has been effective in raising students' awareness of the importance of building a professional image in the digital world. With a better understanding of personal branding, students are expected to leverage social media positively to strengthen their professional reputation and open up career opportunities in the future.